2018
DOI: 10.21608/ejhm.2018.9061
|View full text |Cite
|
Sign up to set email alerts
|

Sonomammography versus MRI in Evaluation of BI-RADS III Breast Lesion

Abstract: Background: Breast cancer is sometimes found after symptoms appear, but many women with breast cancer have no symptoms. This is why regular breast cancer screening is so important, early detection and treatment are the most important strategies to prevent deaths from breast cancer. Breast cancer that's found early, when it's small and has not spread, is easier to treat successfully, regular screening tests are the most reliable way for early detection. Objective: to high light the role of sonomammography versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
0
1
Order By: Relevance
“…A respective sonomammographic sensitivity and specificity of 73% and 80% were achieved in our study which is much higher than the overall reported sensitivity of 30-60 and 40-80 stated by Mehnati et al [5]. However, it is comparative with Eisa et al who reported a sensitivity of 68 and specificity of 74% [19].…”
Section: Discussioncontrasting
confidence: 66%
“…A respective sonomammographic sensitivity and specificity of 73% and 80% were achieved in our study which is much higher than the overall reported sensitivity of 30-60 and 40-80 stated by Mehnati et al [5]. However, it is comparative with Eisa et al who reported a sensitivity of 68 and specificity of 74% [19].…”
Section: Discussioncontrasting
confidence: 66%
“…That was superior to the sensitivity and specificity reported by Mehnati et al in [8], which were 30-60 and 40-80, respectively. Nevertheless, the results in the current study were in reproachment to the findings recorded by Eisa et al in [9] and Hashem et al [7] in their studies, who demonstrated a specificity of 74% and 80%, with sensitivity of 68% and 73%, respectively. These paralogisms in the mammography are mainly attributed to the dense breast cases (ACR III and IV), where the fibro glandular tissue almost conceal any breast lesions, yet aided by ultrasound; their sensitivity and specificity to detect and characterize lesions are relatively higher.…”
Section: Discussionsupporting
confidence: 86%